Viruses to kill insects - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Scientists at the Institute of Virology in Oxford, Great Britain, have come up with a number of baculoviruses which can be used to combat crop-devouring insects. These viruses are added to sugar solutions which, once absorbed by the larvae,...